2012
DOI: 10.2139/ssrn.2129219
|View full text |Cite
|
Sign up to set email alerts
|

Social Spending and Human Development in Selected West African Countries

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Investment in more private institutions, such as clinics and hospitals, is crucial from a management aspect for averagecountry health outcomes. Iheoma (2014) used a fixed effect model using time panel data to analyze the contribution of public health spending to human development in Sub-Saharan African nations. He contended that public health spending explains many of these countries' social development disparities.…”
Section: Public Health Expenditure and Human Development Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Investment in more private institutions, such as clinics and hospitals, is crucial from a management aspect for averagecountry health outcomes. Iheoma (2014) used a fixed effect model using time panel data to analyze the contribution of public health spending to human development in Sub-Saharan African nations. He contended that public health spending explains many of these countries' social development disparities.…”
Section: Public Health Expenditure and Human Development Indexmentioning
confidence: 99%
“…From these findings, we can affirm the positive influence of government expenditure in the education sector on human development and the education sector's priorities in developing countries to impact human development. Iheoma (2014) examined the outcomes of social spending in the education sector on human development in 20 countries in sub-Saharan Africa. After applying the fixed effect estimation method, the results showed that only tertiary education spending influences human development in these countries.…”
Section: Public Spending On Education and The Human Development Indexmentioning
confidence: 99%
“…Penelitian terdahulu yang telah dilakukan, menunjukkan bahwa belanja pemerintah bidang pendidikan dan bidang kesehatan memiliki pengaruh yang signifikan terhadap pembentukan IPM (Ardiningrum et al, 2021;Astri, M., Nikensari, S. I., & Kuncara, 2013;Ernita, 2022;Fattah, S., & Muji, 2012;Gupta, S., Clements, B., & Tjongson, 1998;Halim et al, 2022;Iheoma, 2014;M. J Razmi, 2012;Setyowati, L., & Suparwati, 2012) terdapat pengaruh positif dan signifikan anggaran pendidikan dan anggaran Kesehatan terhadap indeks pembangunan manusia di Indonesia tahun 2015-2019.…”
Section: Pengeluaran Pemerintahunclassified
“…Hal tersebut berarti bahwa pengeluaran pemerintah dibidang Pendidikan dan kesehatan tidak bisa berdiri sendiri dan harus secara bersama-sama. Hal ini senada dengan penelitian (Ardiningrum et al, 2021;Astri, M., Nikensari, S. I., & Kuncara, 2013;Ernita, 2022;Fattah, S., & Muji, 2012;Gupta, S., Clements, B., & Tjongson, 1998;Halim et al, 2022;Iheoma, 2014;M. J Razmi, 2012;Setyowati, L., & Suparwati, 2012).…”
Section: Pembahasan Pengaruh Anggaran Pendidikan Dan Anggaran Kesehat...unclassified